Dance with the Dollar: Exchange Rate Exposure on the German Stock Market - Horst Entorf; Gösta Jamin (Technische Universität Darmstadt, Department of Law and Economics, 2002)
We estimate the Dollar exposure of German DAX corporations. Our results are based on a new time-variant, APT-based and panel econometric extension of the exchange-rate exposure model in the tradition of Adler and Dumas (1984) and Jorion (1990). Our stock market data consist of 28 performance indices of German DAX corporations. We include macroeconomic risk factors, and data on export and import involvement. Dollar exposures turn out to differ between exporters and importers and they are rather unstable over time. In contrast to most previous studies in the literature that find little evidence of exposure, we confirm recent results of Dominguez and Tesar (2001) who report that higher foreign involvement corresponds to higher exposure at least in Germany. Moreover, our findings suggest that exposure also depends on the prevailing level of the Dollar exchange rate.
Keywords: G15; F31; C23; 330; Börsenkurs; Aktienindex; Währungsrisiko; US-Dollar; Arbitrage Pricing; Schätzung; Deutschland